ANALYSIS OF INNOVATION ACTIVITIES OF ENTERPRISES OF KAZAKHSTAN - Zhibek Abylkassimova; Gulnar Orynbekova; Мeirash Alibayeva; Olga Osadchaya (Scientific Journal of Pedagogy and Economics, 2020)
The article noted that the development of the innovation potential of enterprises in the regions of Kazakhstan contributes to the transition of the innovation economy, where goods with high added value will be produced. The article examines the factors affecting the innovation activity of the regions, considers the dynamics of innovation activity and identifies problems and tools for the development of innovative entrepreneurship.